PENGARUH BEBAN KERJA DAN KELELAHAN PERAWAT TERHADAP PERAWATAN INFUS DI RUANG PERAWATAN KELAS IIIRSUD SUKOHARJO - Wiwit Ciptaningsih Haryanto; Elsye Maria Rosa (Universitas Muhammadiyah Yogyakarta, 2014)
Nurses have a big role in infusion installment and care according to the Standard Operating Procedure. Infection or other problems that may emerge during infusion installment can be minimized or avoided as long as the operating standard is met. Quantity work load, qualitative workload, physical workload, psychological workload, social workload and nurses’ fatigue are the major causes of infection due to working errors. This research aims at finding out the effect of nurses’ workload and fatigue on infusion care. This is a quantitative research using cross-sectional approach. The population consists of all nurses working in the third class of RSUD Sukoharjo. Using total sampling, the sampling consists of 28 nurses. Nurses’ workload that influenced infusion care comprises qualitative workload (p 0,000; B -1,847), nurse workload that did not influence infusion care comprised quantitative workload (p 0,109; B -0,243), physical workload (p 0,124; B -0,612), psychological workload (p 0,109; B -0,294), and social workload (p 0,875; B -0,053). There is no effect of nurse fatigue on infusion care (p 0,209; B -0,135). Quantitative workload did not influence nurse fatigue (p 0,196; B -0,367), qualitative workload did not influence nurse fatigue (p 0,053; B -1,331), physical workload did not influence nurse fatigue (p 0,171; B -1,061), and psychological workload did not influence nurse fatigue (p 0,980; B 0,021). The hardest nurse workload that had influenced infusion care in the third class of RSUD Sukoharjo is a qualitative workload. The more a qualitative workload that nurse felt, the worse infusion care they will treat. The workload has no effect on nurse fatigue.